In Search of a Mythical Exception to Privity of Contract in Indian Law - Swaminathan, S (Journal of Malaysian and Comparative Law, 2016)
In a recent judgment, Utair Aviation v Jagson Airlines, the Delhi High Court formulated a novel ‘conduct, acknowledgement and admission’ exception to the privity of contract requirement. Two influential treatises on Indian contract law, Avtar Singh’s Contract and Specific Relief and Frederick Pollock and Dinsha Mulla’s Indian Contract Act 1872 too, recognise the exception and cite a long list of authorities in its support. This article argues that neither is the exception doctrinally warranted—based as it is on a problematic reading of the authorities cited in its favour—nor its invocation in the case or by the treatises justified. The Court’s claim that the ‘width’ of section 2(d) of the Indian Contract Act which, unlike the English definition of consideration, allows consideration to move from the promisee or another person, provides the doctrinal basis for an expanded list exceptions to the privity rule, will be contested. It will also be argued that the purported exception is rendered conceptually redundant by section 2(d) of the Indian Contract Act 1872. The discussion will have for its backdrop, the contrast between the English law and the Indian Contract Act on two cognate ideas, namely, privity of contract and privity of consideration, the conflation of which, it will be argued, engenders some of the confusion in the case under discussion. The rule…is stated in the text-books as based upon the authority of the decision, and afterward, when it offers an easy solution of a difficult case, it is quoted by other judges upon the authority of the text-book, and so, without inquiry into its origin it comes to be regarded as a rule of law; and it is only when it is applied to cases in which it works injustice that the soundness of the rule begins to be questioned. – Edward Quinton Keasby